2020
DOI: 10.1111/jvs.12921
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climate change on treeline trees in Sagarmatha (Mt. Everest, Central Himalaya)

Abstract: Question Tree growth at high altitude in the Himalayan region is limited by cold temperatures and also strongly influenced by the seasonality of the Asian monsoon. Understanding whether the ongoing increase in temperatures and changes in precipitation regimes in the Himalayan region can stimulate or limit tree growth is of particular importance to predict the local treeline dynamics. Location Altitudinal treeline (~4000 m a.s.l.) in the Sagarmatha (Mt. Everest) National Park (Central Himalaya, Eastern Nepal). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 62 publications
4
10
1
Order By: Relevance
“…Several studies across the Nepal Himalaya have reported lower value of Rbar. For example, Rbar values of A. spectabilis in Sagarmatha [10,11,17], Rolwaling [12], and B. utilis chronologies in Sagarmatha [10,11,27], Mustang [14], Langtang and Manasalu [27], all had similar correlation coefficients compared to our results. Pandey et al [11,51] in eastern Nepal, and Dawadi et al [26] in central Nepal, reported much lower Rbar values for both species compared to our results.…”
Section: Tree-ring Chronology and Growth Trendsupporting
confidence: 82%
See 4 more Smart Citations
“…Several studies across the Nepal Himalaya have reported lower value of Rbar. For example, Rbar values of A. spectabilis in Sagarmatha [10,11,17], Rolwaling [12], and B. utilis chronologies in Sagarmatha [10,11,27], Mustang [14], Langtang and Manasalu [27], all had similar correlation coefficients compared to our results. Pandey et al [11,51] in eastern Nepal, and Dawadi et al [26] in central Nepal, reported much lower Rbar values for both species compared to our results.…”
Section: Tree-ring Chronology and Growth Trendsupporting
confidence: 82%
“…For example, Harsch et al [9] reported 57% of worldwide treelines (including latitudinal) experiencing warming have advanced upslope and seen increases in recruitment. The Himalayas are experiencing greater warming than the global mean [7,8,[10][11][12]. Forecasted warming is expected to bring dynamic changes to temperature sensitive subalpine plant communities [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations